2016
DOI: 10.1007/s00101-016-0242-8
|View full text |Cite|
|
Sign up to set email alerts
|

Intensivtherapie nach aneurysmatischer Subarachnoidalblutung

Abstract: Aneurysmal subarachnoid hemorrhage (SAH) is a devastating disease and nearly one third of patients die in the acute phase. Due to the bleeding event, a hyperactive sympathetic nervous system and an uncontrolled inflammatory response have a profound local and systemic impact on other organ functions. Neuroendocrinological disorders and cardiopulmonary morbidity are dominant. Despite a decrease in hospital mortality for high volume centers, a high proportion of survivors suffer from neurological deficits. Knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…As a lipophilic vasodilator, we expected nimodipine to cause cerebrovascular dilation with elevated CBF and rSO 2 . Due to its low bioavailability and in accordance with previous studies 1,2,10) , it is conceivable that the gastric administration of nimodipine failed to attain therapeutic plasma concentrations needed to achieve the desired effect. However, in this clinical study, nimodipine plasma concentrations were not measured and hence a dose-effect relation cannot be analyzed.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…As a lipophilic vasodilator, we expected nimodipine to cause cerebrovascular dilation with elevated CBF and rSO 2 . Due to its low bioavailability and in accordance with previous studies 1,2,10) , it is conceivable that the gastric administration of nimodipine failed to attain therapeutic plasma concentrations needed to achieve the desired effect. However, in this clinical study, nimodipine plasma concentrations were not measured and hence a dose-effect relation cannot be analyzed.…”
Section: Discussionsupporting
confidence: 52%
“…If clinically significant DCI occurs, arterial hypertension is recommended to improve cerebral perfusion 12) . While several studies report increased cerebral blood flow (CBF) due to nimodipine, few show reduced CBF linked to decreased MAP and CPP 5,10,16) . In contrast, one retrospective study even revealed an enhanced risk of CVS with a higher need for vasopressor agents associated with nimodipine administration 10) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations